Increased awareness of knowledge in anticipation of health problems through socialization and blood type examination - Wahyu, Rysna; Jenice Sanaky , Marisca; Muthiyah A. AM, Andi; Sofiantin, Nuril; Nur Fadillah, Sakinah (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Blood type examination is a laboratory procedure performed to determine blood type. In the pretransfusion test, the minimum blood type examination that must be done is the ABO and Rhesus system blood types. Blood type detection is done to determine the blood type in the body. The method used in this activity is the action research method with a participatory action program approach involving high school students. This community service can be achieved, namely students can understand the purpose of blood type examination and provide blood type checks so that students know their blood type has been achieved, considering the importance of individuals knowing blood type and knowing the functions and benefits of blood in the human body